Results from a pilot study: The effects of nicotinamide riboside on mild cognitive impairment: Human/Human trials: Nutraceuticals and non‐pharmacological interventions. (7th December 2020) - Orr, Miranda E.; Kotkowski, Eithan; Bair‐Kelps, Darcy; Romo, Terry; Espinoza, Sara; Musi, Nicolas; Powers, Becky; ,
Abstract: Background: Nicotinamide adenine dinucleotide (NAD+) is a critical coenzyme in cellular metabolism. NAD(+) levels decrease with aging. Experimentally boosting NAD(+) improves cognitive function and synaptic plasticity in Alzheimer's disease mouse models. NAD(+) can be synthesized from dietary intake of its precursors, including nicotinamide riboside (NR), a readily available non‐prescription nutritional supplement. Recent studies have demonstrated that dietary NR increases blood NAD(+) levels in healthy older adults. We hypothesize that NR supplementation will positively affect brain function in older adults with mild cognitive impairment (MCI). Method: Phase 2 randomized, double‐blind, placebo‐controlled trial with a 10‐week treatment period. Adults aged ≥65‐years‐old with a prior diagnosis of normal cognition [Montreal Cognitive Assessment (MoCA) score 26‐30] or MCI (MoCA score of 21‐25) participated at UT Health San Antonio. Dose escalation with NR over a 4‐week period was used to reach 1g/day, or maximum tolerated dose, for the final 6 weeks of the study. The primary outcomes were change from baseline on the MoCA and hippocampal blood flow as assessed by functional MRI (fMRI). Secondary outcomes included psychometric and frailty measures. Levels of blood NAD(+) and metabolites were determined at baseline and at the end of the study. Result: Baseline levels of NAD(+) did not significantly differ between MCI and control groups (21.4 ± 0.75 versus 19.3 ± 2.04μM, mean ± SEM, MCI and control, respectively; p = 0.24). NR was well tolerated and significantly increased blood NAD(+), NAAD, and Me4PY (log2 fold change: 1.2, 2.6, 3.3, respectively; p < 0.0001). NR treatment was associated with positive functional changes in the brain and frailty measures, but changes in cognitive measures were not observed. Conclusion: A 10‐week supplementation of NR was well tolerated and significantly increased NAD(+) and associated metabolites in the blood of older adults with MCI. NR improved fMRI and physical function, our primary and secondary outcome measures, respectively. However, differences in cognition were not achieved in this small pilot study. Our results provide supporting evidence for further testing of NR as a method to maintain brain structure and function in older adults with MCI.